A química ambiental sob a ótica dos alunos do curso técnico integrado em mineração do IFAP - (:unkn) unknown (Brasil, 2020)
Environmental Chemistry is the area of science which studies the chemical processes that occur in the environment, which can be caused by man or in a natural way. Its relevance is growing, regarding the constant environmental and social instabilities on the planet, which makes necessary the intensification of the environmental focus on education. The main objective of this article is to understand the perception of students of the Integrated Technical Course in Mining about environmental chemistry. This is a study based on qualitative and quantitative research. The target audience was a class from the 2nd grade of the IFAP Mining Technician course. The data collection happened in September 2019, through the application of a semi-structured questionnaire. The results showed that a good part of the respondents has a perception, even basic, of the importance of Environmental Chemistry, although not everyone knows its close relationship with economic and technological development. Therefore, the present discussion in this study can be useful for researchers, teachers, students and the public in general, as they offer results that can contribute to minimize some gaps that still exist in teaching and learning process in Chemistry.
Environmental chemistry under the view of the students of the integrated technical course in mining at IFAP
Keywords: Ensino de Química; Química Ambiental; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA